A one-pot and three-component synthetic approach for the preparation of asymmetric and multi-substituted 1, 4-dihydropyrazines. Issue 47 (21st November 2019) - Peytam, Fariba; Adib, Mehdi; Shourgeshty, Reihaneh; Rahmanian-Jazi, Mahmoud; Jahani, Mehdi; Larijani, Bagher; Mahdavi, Mohammad
Graphical abstract: Abstract: An efficient, one-pot and three-component synthesis of a new series of 2-acyl-3, 4, 6-triaryl-1, 4-dihydropyrazines is described. This two-step strategy involves treatment of phenacyl bromides and anilines to give the nucleophilic substitution intermediate followed by Michael-addition-cyclization to α -azidochalcones to afford the title compounds in high yields.